Natural and constrained language production as a function of age and cognitive abilities - Rabaglia, Cristina D. (2011)
Although it is often claimed that verbal abilities are relatively well maintained across the adult lifespan, certain aspects of language production have been found to exhibit cross-sectional differences and longitudinal declines. In the current project age-related differences in controlled and naturalistic elicited language production tasks were examined within the context of a reference battery of cognitive abilities in a moderately large sample of individuals aged 18–90. The results provide support for age-related increases in lexical sophistication and diversity at the discourse level, and declines in grammatical complexity in controlled and naturalistic contexts. Further, age-related decreases in facility with complex grammatical constructions in controlled sentence production were statistically independent of the cognitive abilities assessed in this project.